### Related

##### sublis

ex1: (2*a*x - 5*a) / ...

sublis([a=0.90, x=7.7...

Calculate

##### sublis

sa (e) := sublis ([a ...

sb (e) := sublis ([a ...

sa (sb (sa (sb (a))));

Calculate

##### sublis

sublis([sigma1=0.357,...

Calculate

##### sublis-subst

eq1: a = in - out;

eq2: b = a*K1 + a*K2/...

eq3: g = 1/(s^2+3*s+1);

Calculate

##### sublis

sa (e) := sublis ([a ...

sb (e) := sublis ([a ...

sa(sb(sa(sb(sa (sb (b...

Calculate

##### sublis

solvesust(F, y) := su...

Calculate

##### sublis

sa (e) := sublis ([a ...

sb (e) := sublis ([a ...

sa(sb(sa(sb(sa (sb (a...

Calculate

##### sublis

ex1: (2*a*x - 5*a) / ...

sublis([a=0.9, x = 7....

Calculate

##### sublis

sublis([sigma1=0.357,...

Calculate

##### sublis

sa (e) := sublis ([a ...

sb (e) := sublis ([a ...

sb (sa(sb (sa (sb (sa...

Calculate

### sublis

Run Example
(%i1)sublis([Cx=0,Cy=0,Bx=4*a,By=0,Ax=(2*c^2-2*b^2+2*a^2)/a,Ay=2*sqrt(-c^4+2*b^2*c^2+2*a^2*c^2-b^4+2*a^2*b^2-a^4)/a,Ex=3*(2*c^2-2*b^2+2*a^2)/(4*a),Ey=3*sqrt(-c^4+2*b^2*c^2+2*a^2*c^2-b^4+2*a^2*b^2-a^4)/(2*a),Fx=((2*c^2-2*b^2+2*a^2)/a-4*a)/4+4*a,Fy=1/2*sqrt(-c^4+2*b^2*c^2+2*a^2*c^2-b^4+2*a^2*b^2-a^4)/a,Gx=a,Gy=0],(Ey-By)*(x-Bx)/(Ex-Bx)+By);
4      2  2      2  2    4      2  2    4
3 sqrt(- c  + 2 b  c  + 2 a  c  - b  + 2 a  b  - a ) (x - 4 a)
(%o1)   --------------------------------------------------------------
2      2      2
3 (2 c  - 2 b  + 2 a )
2 a (---------------------- - 4 a)
4 a
(%i2)
Run Example
f(theta):=((cos(theta)^2-sin(theta)*(sin(theta)-zeta))/sqrt(lambda^2-(sin(theta)-zeta)^2));
2
cos (theta) - sin(theta) (sin(theta) - zeta)
(%o1)      f(theta) := --------------------------------------------
2                      2
sqrt(lambda  - (sin(theta) - zeta) )
(%i2) trigreduce(f(theta));
sqrt(2) sin(theta) zeta
(%o2) ----------------------------------------------------------------
2         2
sqrt(2 lambda  - 2 zeta  + 4 sin(theta) zeta + cos(2 theta) - 1)
sqrt(2) cos(2 theta)
+ ----------------------------------------------------------------
2         2
sqrt(2 lambda  - 2 zeta  + 4 sin(theta) zeta + cos(2 theta) - 1)
(%i3) plt2d(sublis([lambda=3.5,zeta=0.3],f(theta)),[theta,-%pi,%pi]);
2
cos (theta) - (sin(theta) - 0.3) sin(theta)
(%o3) plt2d(-------------------------------------------, [theta, - %pi, %pi])
2
sqrt(12.25 - (sin(theta) - 0.3) )
(%i4)
Run Example
sa (e) := sublis ([a = -a, b = a+b], e);
(%o1)              sa(e) := sublis([a = - a, b = a + b], e)
(%i2) sb (e) := sublis ([a = a+b, b = -b], e);
(%o2)              sb(e) := sublis([a = a + b, b = - b], e)
(%i3) sa (sb (sa (sb (sa (a)))));
(%o3)                                b + a
(%i4)

Help for Sublis